PENGARUH GAYA KEPEMIMPINAN MELAYANI DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI DI KECAMATAN MAGELANG UTARA KOTA MAGELANG DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING - Nur Widiastuti; Selamat Riauwanto; Christina Anik Harwati (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2022)
The purpose of this research was to analyze the influence and the relations among four variables which are Leader serving style, workload, working motivation and work satisfactions as elements of variable which are used as variables mediation between free variable with bound variable. This research was conducted at North Magelang Distric Government office using method correlational with quantitative methods. Technic nonprobable sampling was used to collect data of 104 respondents during Sample collecting process.Data obtained distributing questionnaires then analyzed using multiple linear regression and hypothesis testing using SPSS IBM version 22. Result showed that hypothesis was proved as seen as positive and significant correlation among three free variables to bounded variables. Meanwhile on correlation among Serving Leader style, work satisfaction and work motivation those could not be used as variable mediation, which meant work motivation could not be used as variable intervening.